PENGARUH KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT. RIAU POS INTERMEDIA DI KOTA PEKANBARU - Dewi, Diana Sri (Eko dan Bisnis: Riau Economic and Business Review, 2021)
This research was conducted at PT. Riau Pos Intermedia Pekanbaru located on HR.Soebrantasstreet KM. 10.5 Pekanbaru. This study aims to determine the influence of leadership on employee performance at PT. Riau PosIntermedia Pekanbaru.In analyzing the data obtained from the research object using descriptive analysis and quantitative analysis using SPSS program. Based on the results in this study can be concluded that leadership has a significant and positive impact on employee performance at PT. Riau Pos Intermedia Pekanbaru. .From the regression results in this study, can be seen the regression equation as follows: Y = 15.714 + 0.946 X. This means that the value of a is 15.714 this value shows that when the variable Leadership (variable X) is zero, then Performance (variable Y) of 15.714. While the value of b is 0.946, meaning that when an increase in the value of Leadership variable (variable X) of 1 (one) unit then Performance (variable Y) will increase by 0.946 units.The result of t test is known that t count (6,527)> t table (2.03224) and significance (0,000) <0,05. Thus Ho is rejected and Ha accepted. This means that there is a significant influence of leadership variables on employee performance at PT. Riau Pos Intermedia Pekanbaru. The direction of its influence is positive. This means that the better the leadership will improve employee performance at PT. Riau Pos Intermedia Pekanbaru.The coefficient of determination (R Â²) is 0,556. Means the relationship between independent variables (leadership) to the dependent variable (performance) of 55.6%. While the remaining 44.4% influenced by other variables that are not included in this study.